Textual masculinity and the exchange of women in Renaissance Venice - Quaintance, Courtney, 1968- (Toronto Italian studies., 2015)
Based on archival work and Quaintance's exceptional knowledge of Venetian dialect poetry, Textual Masculinity and the Exchange of Women in Renaissance Venice is an unprecedented window into the understudied world of Venetian literature.